A Case of Postoperative SMART Syndrome in a Medulloblastoma Survivor - Cirjan, Cristian; Jamal, Ali; Mercier, Philippe; Berkovich, Rachel; Navalkele, Pournima (Journal of Child Science, 2021)
Stroke-like migraine attacks after radiation therapy (SMART) syndrome is a rare neurological phenomenon characterized by reversible symptoms of headache, seizure, hemiparesis, and visual changes associated with a remote history of cranial irradiation. We describe a case of a medulloblastoma survivor, presenting with postoperative neurological deficits, along with neuroimaging findings and subsequent resolution of symptoms, highly suggestive of SMART syndrome. We have also reviewed the common epidemiological and diagnostic factors associated with this rare disease, as well as discussed pathophysiological mechanisms.
Keywords: radiation; migraine; stroke; SMART syndrome